Cell Intrinsic Deregulated ß-Catenin Signaling Promotes Expansion of Bone Marrow Derived Connective Tissue Type Mast Cells, Systemic Inflammation, and Colon Cancer - Saadalla, Abdulrahman; Lima, Mariana Machado; Tsai, Funien; Osman, Abu; Singh, Mahendra Pal; Linden, David R.; Dennis, Kristen L.; Haeryfar, S. M. Mansour; Gurish, Michael F.; Gounari, Fotini; Khazaie, Khashayarsha (Frontiers in Immunology, 2019)
Mast cells constitutively express ß-catenin and expand in solid tumors such as colon and skin cancer. However, the role of ß-catenin signaling in mast cells and the cause or effect of mast cell expansion and tumor growth has yet to be established. In earlier studies we used mast cell depletion and protease staining approaches, to provide evidence for a causative role of mast cells in small bowel polyposis, and related specific phenotypes and distributions of tumor infiltrating mast cells to stages of tumor growth. Here we report that, stabilization of ß-catenin expands mast cells to promote high incidence of colon polyposis and infrequent small bowel polyps and skin cancer. Expression of a dominant acting ß-catenin in mast cells (5CreCAT) stimulated maturation and expression of granule stored proteases. Both mucosal and connective tissue type mast cells accumulated in colonic small bowel polyps independent of gender, and mice developed chronic systemic inflammation with splenomegaly. Reconstitution of polyposis-prone mice with bone marrow from 5CreCAT mice resulted in focal expansion of connective tissue like mast cells, which are normally rare in benign polyps and characteristically expand during adenoma-to-carcinoma transition. Our findings highlight a hitherto unknown contribution of ß-catenin signaling in mast cells to their maturation and to increased risk of colon cancer.